Rekonfigurasi Batas Diskresi Pejabat Administrasi Pasca Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Sandra Leoni Prakasa Yakub; Santi Suryani; Fitriyani Yuliawati; Muhamad Reza Atqia; Wili Suminar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the position of statutory regulations as the main limiting framework for administrative discretion in Indonesian administrative law, particularly after the enactment of Law Number 11 of 2020 on Job Creation. The main issue examined is the normative shift caused by the removal of the requirement that discretion must not contradict statutory regulations, which potentially weakens legal certainty and judicial control. This research uses a normative juridical method with a regulatory and conceptualization approach, and is supported by the theory of discretionary justice, balance of legal objectives, and good governance. The findings indicate that the elimination of formal legality requirements transforms discretion from a legally constrained authority into a broader administrative freedom, increasing the risk of abuse of power and weakening the objective standards of judicial review in administrative courts. The study concludes that such a shift undermines the core principles of the rule of law and necessitates constitutional review to restore legal certainty, accountability, and effective judicial oversight.